On reliability modeling and evaluating in cloud services system - Telenyk, S.F.; Savchuk, O.V.; Pokrovskyi, E.O.; Morgal, O.M.; Pokhylenko, O.A. (Штучний інтелект, 2018)
A typical system of reliability of cloud services with a cloud management system is explored. The proposed model is service-oriented and hierarchical. It includes two phases of query maintenance: 1) time-out and overflow; 2) execution. The model is described by the system of Chapman-Kolmogorov equations. The final stage of the process is protection of user requests and results of tasks execution. An approach to cloud data security is proposed which, unlike traditional approaches, guarantees confidentiality and security of information even at compromising the provider of cloud service or its infrastructure.